Mixture interactions at mammalian olfactory receptors are dependent on the cellular environment - Elizabeth A. Corey (Nature Portfolio, 2021)
Abstract Functional characterization of mammalian olfactory receptors (ORs) remains a major challenge to ultimately understanding the olfactory code. Here, we compare the responses of the mouse Olfr73 ectopically expressed in olfactory sensory neurons using AAV gene delivery in vivo and expressed in vitro in cell culture. The response dynamics and concentration-dependence of agonists for the ectopically expressed Olfr73 were similar to those reported for the endogenous Olfr73, however the antagonism previously reported between its cognate agonist and several antagonists was not replicated in vivo. Expressing the OR in vitro reproduced the antagonism reported for short odor pulses, but not for prolonged odor exposure. Our findings suggest that both the cellular environment and the stimulus dynamics shape the functionality of Olfr73 and argue that characterizing ORs in ‘native’ conditions, rather than in vitro, provides a more relevant understanding of ligand-OR interactions.